1983
DOI: 10.1139/b83-407
|View full text |Cite
|
Sign up to set email alerts
|

Seed demography

Abstract: "Some seeds fell by the way side, … some fell upon stony places,... and some fell among thorns;.... but other fell into good ground" (The Bible, St. Matthew's gospel, Chapt. 13).Much of modern plant ecology is concerned with demography. One major topic is the study of mortality rates. A common belief, originating with Charles Darwin's Origin of Species is that the seedling stage of the plant's life cycle exhibits the highest mortality rates. Evidence is provided in this paper to show that the highest rates of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
83
0
9

Year Published

1986
1986
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(93 citation statements)
references
References 0 publications
1
83
0
9
Order By: Relevance
“…71: '77l-'782. L'importance des graines produites par le Linaria vulgaris dans I'augmentation de la s6v6rit6 des infestations a 6t6 6valu6e en Alberta en 1988 et 1989. Les infestations 6tablies le 17 mai 1988 i partir de morceaux de racines de 10 cm de long avec une tige de 10 cm de hauteur sur des parcelles en jachbre ou sem6es avec de l'orge ont commenc6es ir fleurir't'72 CANADIAN JOURNAL OF PLANT SCIENCE A large number of seeds are produced by most plant species, but only a small percentage successfully establish as seedlings (Cavers 1983).…”
unclassified
“…71: '77l-'782. L'importance des graines produites par le Linaria vulgaris dans I'augmentation de la s6v6rit6 des infestations a 6t6 6valu6e en Alberta en 1988 et 1989. Les infestations 6tablies le 17 mai 1988 i partir de morceaux de racines de 10 cm de long avec une tige de 10 cm de hauteur sur des parcelles en jachbre ou sem6es avec de l'orge ont commenc6es ir fleurir't'72 CANADIAN JOURNAL OF PLANT SCIENCE A large number of seeds are produced by most plant species, but only a small percentage successfully establish as seedlings (Cavers 1983).…”
unclassified
“…Le groupe des cohortes de 1994 représente encore 9 % des semis après 12 ans de suivi, soit 3 individus m" , alors que la cohorte de 1995 représente 5 % de la banque de semis, soit 1,7 serai m" Pendant une année semencière, une bonne partie des graines peuvent être vides en raison d'un manque de pollinisation (Houle 1999, Cavers 1983. Des graines étaient peutêtre détruites par les conditions environnementales, la prédation, le parasitisme des cônes, le froid, la dessiccation et les attaques microbiennes (Cavers 1983).…”
Section: Présentation Des Cohortes Présentes En 2006unclassified
“…According to Whitmore (1983), light, followed by temperature, in wet tropical forests is the most important factor for the start of germination. Requirements for germination reported in literature indicated that pioneer species could germinate in the grassland (Vázquez-Yanes, 1976;Gómez-Pompa and Vázquez-Yanes, 1976;Harper, 1977;Silvertown, 1982;Cavers, 1983;Whitmore, 1983Whitmore, , 1990Fenner, 1985;1993;Fleming and Williams, 1990). Then one may ask: why seeds in the pasture do not germinate on the site?…”
Section: Potential and Limitations Of Seed Bank In The Succession Promentioning
confidence: 99%
“…Recently arrived seeds from seed rain form a small amount of the seed bank. Since in dispersion, a progressive decrease in seed concentration occurs in proportion to distance from sources (forests) (Cavers, 1983;Saulei and Swaine, 1988;Alvarez-Buylla and Garay, 1994) and given the proper conditions for the start of seed germination in pasture (light, temperature, humidity etc), they could quickly germinate and thus be excluded from sampling. Cecropia obtusifolia seeds are dispersed by birds and mammals.…”
Section: Potential and Limitations Of Seed Bank In The Succession Promentioning
confidence: 99%